Real Exchange Rate, Exchange Rate Volatility and Trade Balance in Sub-Saharan African Countries: A Generalized Method of Moment (GMM) Approach (International Journal of Scientific Research and Management (IJSRM), 2017)
This study examines the effect of real exchange rate and exchange rate volatility on trade balance in Sub-Saharan African countries from 2006 to 2016. Fourteen countries in the region are selected for the study. Generalized Method of Moment (GMM) is used as the estimation technique, and exchange rate volatility is generated from real exchange rate using Generalized Autoregressive Conditional Heteroskedasticity (GARCH). The result shows that real exchange rate and exchange rate volatility have positive and significant effect on trade balance in sub-Saharan African countries. Furthermore, gross domestic product (domestic income) has positive and significant effect on trade balance while world gross domestic product (foreign income) has negative effect on trade balance. The study concludes that the region should take advantage of exchange rate volatility in improving their trade balance